Plan de negocios para la creación de una Baber Shop en la ciudad de Ambato, con la aplicación de las mejores prácticas internacionales de este tipo de establecimiento - Vayas Hidalgo, Francisco Josué (2017)
The following business plan is focused on creating an exclusive place for the treatment and hair and facial care of men's beauty in the city of Ambato, seeks to be a pioneer in offering this service; For the service offer a local is created in the city, in the neighborhood Ficoa, where customers can be constantly served. It should be emphasized that the masculine care regarding the physical appearance in the last years has been having a gradual growth, reason for which the project has taken this object as main reason for the creation of the same one. In addition, having conducted a market research, corroborates the need for this service for citizens. With this, the primary objective of the project seeks to be a new and differentiated alternative, thus promoting, that the physical care of the man is greater. Consequently, and based on the financial analysis carried out, it shows all the necessary characteristics of a positive viability, the project in the five years of projection generates economic returns, with a tendency for them to be increasing.